Outcome of cardiac surgery in patients with low preoperative ejection fraction. Issue 1 (December 2016) - Pieri, Marina; Belletti, Alessandro; Monaco, Fabrizio; Pisano, Antonio; Musu, Mario; Dalessandro, Veronica; Monti, Giacomo; Finco, Gabriele; Zangrillo, Alberto; Landoni, Giovanni
Abstract Background In patients undergoing cardiac surgery, a reduced preoperative left ventricular ejection fraction (LVEF) is common and is associated with a worse outcome. Available outcome data for these patients address specific surgical procedures, mainly coronary artery bypass graft (CABG). Aim of our study was to investigate perioperative outcome of surgery on patients with low pre-operative LVEF undergoing a broad range of cardiac surgical procedures. Methods Data from patients with pre-operative LVEF ≤40 % undergoing cardiac surgery at a university hospital were reviewed and analyzed. A subgroup analysis on patients with pre-operative LVEF ≤30 % was also performed. Results A total of 7313 patients underwent cardiac surgery during the study period. Out of these, 781 patients (11 %) had a pre-operative LVEF ≤40 % and were included in the analysis. Mean pre-operative LVEF was 33.9 ± 6.1 % and in 290 patients (37 %) LVEF was ≤30 %. The most frequently performed operation was CABG (31 % of procedures), followed by mitral valve surgery (22 %) and aortic valve surgery (19 %). Overall perioperative mortality was 5.6 %. Mitral valve surgery was more frequent among patients who did not survive, while survivors underwent more frequently CABG. Post-operative myocardial infarction occurred in 19 (2.4 %) of patients, low cardiac output syndrome in 271 (35 %). Acute kidney injury occurred in 195 (25 %) of patients. Duration of mechanical ventilation was 18 (12–48) hours. Incidence of complications was higher in patients with LVEF ≤30 %. Stepwise multivariate analysis identified chronic obstructive pulmonary disease, pre-operative insertion of intra-aortic balloon pump, and pre-operative need for inotropes as independent predictors of mortality among patients with LVEF ≤40 %. Conclusions We confirmed that patients with low pre-operative LVEF undergoing cardiac surgery are at higher risk of post-operative complications. Cardiac surgery can be performed with acceptable mortality rates; however, mitral valve surgery, was found to be associated with higher mortality rates in this population. Accurate selection of patients, risk/benefit evaluation, and planning of surgical and anesthesiological management are mandatory to improve outcome.